Activity of immune checkpoint inhibition in platinum refractory germ-cell tumors - Zschäbitz, Stefanie; Lasitschka, Felix; Jäger, Dirk; Grüllich, Carsten (Annals of oncology, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.The outcome of patients with platinum refractory germ cell cancer who relapse after or are no candidates for stem-cell transplantation is dismal. No significant progress has been made within the last years. The use of anti-PD-1 antibodies has led to complete remissions and long-term disease control in patients with non-small-cell lung cancer, renal cell carcinoma, and malignant melanoma with metastasized disease [1-3]. Recently, PD-L1 expression in testicular germ-cell tumor samples has been described [4, 5]....We report on the clinical course of four heavily pretreated patients with platinum refractory germ-cell tumors for whom no more curative standard existed and who received checkpoint inhibitors (anti-PD-1 antibodies). Detailed characteristics of pretreatment schedules are given in Table 1 (patients 3 and 4)...
Gesehen am 19.01.2018